2014
DOI: 10.1186/s13550-014-0028-4
|View full text |Cite
|
Sign up to set email alerts
|

Could 18 F-DPA-714 PET imaging be interesting to use in the early post-stroke period?

Abstract: BackgroundCerebral stroke is a severe and frequent condition that requires rapid and reliable diagnosis. If administered shortly after the first symptoms manifest themselves, IV thrombolysis has been shown to increase the functional prognosis by restoring brain reperfusion. However, a better understanding of the pathophysiology of stroke should help to identify potential new therapeutic targets. Stroke is known to induce an inflammatory brain reaction that involves overexpression of the 18-kDa translocator pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
77
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(84 citation statements)
references
References 39 publications
7
77
0
Order By: Relevance
“…For example, activated microglia can be visualized in humans by using a PET ligand that binds to microglia translocator protein or by using a PET tracer ( l -deuteriodeprenyl) to reveal reactive astrocytes during brain inflammation. 111,112 Ultrasmall superparamagnetic iron oxide contrast agent-enhanced MRI can be used to study the role of macrophages in the development of ischaemic lesions in experimental ischaemia and human stroke. 113115 This approach can shed light on the roles of these cells after onset of ischaemia, and could determine when immune status is altered after disease onset by revealing morphological features of the cells.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…For example, activated microglia can be visualized in humans by using a PET ligand that binds to microglia translocator protein or by using a PET tracer ( l -deuteriodeprenyl) to reveal reactive astrocytes during brain inflammation. 111,112 Ultrasmall superparamagnetic iron oxide contrast agent-enhanced MRI can be used to study the role of macrophages in the development of ischaemic lesions in experimental ischaemia and human stroke. 113115 This approach can shed light on the roles of these cells after onset of ischaemia, and could determine when immune status is altered after disease onset by revealing morphological features of the cells.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…14, 15 Initial evaluation of this radiopharmaceutical in healthy human volunteers validated its biodistribution profile towards TSPO. 16 Clinical PET studies using [ 18 F]1 were further conducted on patients with amyotrophic lateral sclerosis, 17 post-stroke 18 and AD, 19 demonstrating this ligand may be useful in assessing the extent of neuroinflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Recent preclinical studies (7-9) have identified 18 F-DPA-714 as a promising TSPO ligand for in vivo imaging, and 18 F-DPA-714 has been used to quantify TSPOs in healthy subjects (10) and in amyotrophic lateral sclerosis, Alzheimer, or stroke patients (11)(12)(13). In most studies, quantification was performed without arterial samples or metabolite analysis and was based either on a simplified compartmental model (the cerebellum as a reference region (10,12)) or on a cluster analysis (10,11,13).…”
mentioning
confidence: 99%
“…In most studies, quantification was performed without arterial samples or metabolite analysis and was based either on a simplified compartmental model (the cerebellum as a reference region (10,12)) or on a cluster analysis (10,11,13).…”
mentioning
confidence: 99%